Legal Protection Effort Against Children In Sale And Purchase Of Cigarettes In Gorontalo Utara Regensy - fitra pakaya (Estudiante Law Journal, 2019)
The current research aims at finding out efforts performed to provide legal protection to children in the sale and purchase of cigarettes in Gorontalo Utara Regency. In addition, the research notifies the inhibiting factors during the provision of legal protection to children in the sale and purchase of cigarettes. The research applies empirical legal research with qualitative descriptive analysis technique. The data used are empirical and secondary data in which they are collected by using techniques of interview and observation. The research finding reveals that there are two efforts of legal protection to children in the sale and purchase of ciragettes, namely cigarettes sales ban to the children and specific protection. In the meantime, the inhibiting factors during the provision of legal protection to children in the sale and purchase of ciragettes are ineffectiveness of regulation, lack of knowledge on the law, absence of counseling and supervision from government, and ineffectiveness of existing programs.